A Unified Model for Fibers With Divergent Pullout Behaviors in Strain Hardening Cementitious Composites (SHCC) - She, Peiyun; Wang, Jiajie; Pang, Zhiming; Lu, Cong (Frontiers in Materials, 2022)
Strain Hardening Cementitious Composites (SHCC) are materials exhibiting high tensile ductility with the formation of multiple cracks. Since the mechanical properties of SHCC members are governed by the interfacial characteristics between fibers and matrix, understanding the mechanism of single fiber pullout behavior is crucial for SHCC material design. Existing model was set up based on Polyvinyl Alcohol (PVA) fibers, making it inapplicable to other kinds of synthetic fibers those exhibit divergent pullout behaviors. As a result, the simulated curves cannot agree well with the tested results of SHCC made with other fibers or hybrid fibers. In this study, a unified single fiber pullout model was proposed to take divergent kinds of fiber pullout behavior into account. Five parameters were defined to describe the single fiber pullout behavior, where the frictional strength during the pullout stage and the blocking length of fiber under pulley force were for the first time introduced. For verification purpose, fiber-pullout samples with Polyethylene Terephthalate (PET) and PVA fibers were tested and the results agree well with the simulated curves from proposed model. The stochasticity of each parameters were then analyzed and described by normal distribution, through which fibers with various random pullout behaviors can be incorporated into a larger scale modelling. Therefore, the fiber-bridging constitutive law for a single crack was calculated and compared with the single crack test results, which confirmed again the validity of the proposed model.